MODEL PEMBELAJARAN MELALUI MEDIA SCHLANGENLEITERSPIEL UNTUK PENINGKATAN KEMAMPUAN BERBICARA GURU BAHASA JERMAN - Kharis, M. (Universitas Negeri Yogyakarta, 2010)
The activity of public service or social devotion is aimed at improving the speaking skills among German teachers in high schools in Malang through schlangenleiterspiel. This way is to facilitate their teaching through Rollenspiel to make their class more interesting and fun. The method used to solve the problems in this activity covers speech, training, question answer, with the theme of